2017
DOI: 10.1177/1940161217723150
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Competitiveness, and Candidate Visibility in Newspaper Coverage of Canadian Party Leadership Contests

Abstract: Are women politicians who mount competitive campaigns for high political office as visible and prominent in news coverage of their candidacies as their male competitors? Few studies have systematically or longitudinally investigated the relationship between candidate gender, competitiveness, and media visibility during election or party leadership campaigns. Moreover, studies of media visibility tend to focus exclusively on the presence of candidates in news stories, as measured by one or more mentions per sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 49 publications
0
17
0
3
Order By: Relevance
“…Thus, examining age, Midtbo (2011) and Veblen (1981) concluded that younger politicians receive more coverage than older colleagues. Wagner et al (2017) found that gender did not influence the media visibility of party leadership hopefuls in Canada. But political communication research in Europe show that women politicians receive less coverage than their male counterparts (Hooghe et al 2015), while in Nigeria political reporting shows a gender differential that is heavily skewed in favor of men (Omojola and Morah 2014).…”
Section: Theorizing Visibility Of Political Actors In National Pressmentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, examining age, Midtbo (2011) and Veblen (1981) concluded that younger politicians receive more coverage than older colleagues. Wagner et al (2017) found that gender did not influence the media visibility of party leadership hopefuls in Canada. But political communication research in Europe show that women politicians receive less coverage than their male counterparts (Hooghe et al 2015), while in Nigeria political reporting shows a gender differential that is heavily skewed in favor of men (Omojola and Morah 2014).…”
Section: Theorizing Visibility Of Political Actors In National Pressmentioning
confidence: 90%
“…In a Kenyan context, ethnic group affiliation is a noninstitutional characteristic explored by Ireri (2012). Age and gender have especially been widely examined (van Aelst et al 2008; Wagner et al 2017). Studies by Tsfati et al (2010) and Waismel-Manor and Tsfati (2011) have examined attractiveness of a politician.…”
Section: Theorizing Visibility Of Political Actors In National Pressmentioning
confidence: 99%
“…Tales son los casos de las elecciones alemanas de 2005 (Semetko & Boomgaarden, 2007) y las primarias presidenciales de 2008 en Estados Unidos (Fernández García, 2010). De acuerdo con estos trabajos, la equidad de cobertura se ha mantenido estable en los últimos 20 años en países anglosajones (Kittilson & Fridkin, 2008), así como en Holanda (Bijker, 2015) y Canadá (Wagner, Trimble, Sampert & Gerrits, 2017).…”
Section: Encuadre 1: Visibilidadunclassified
“…This case is interesting as it provides us with a rare opportunity to assess the coverage of female candidates in North America without having to control for the imbalance between the number of female and male candidates, meaning that journalists had nearly as many opportunities to discuss the campaigns of men and women. In fact, given that the heightened presence of female candidates for the first time in the province was heavily underlined by the media, one could expect that the novelty of the increased presence of female politicians would have been at the forefront of journalists’ minds throughout the campaign (Wagner et al, 2017). Given these exceptional circumstances, what can be said about the way female candidates are treated by the media when they are, for the first time, nearly as numerous as male candidates?…”
Section: Introductionmentioning
confidence: 99%
“…Second, it focuses on a case where the sheer number of female candidates was perceived as an historical achievement and a salient feature of the election. As Wagner et al (2017) note, novel candidates who are considered to be the first to achieve something generate greater media attention. In other words, this case presents opportunities that should be advantageous to women when it comes to media visibility.…”
Section: Introductionmentioning
confidence: 99%